São Paulo e os sentidos da colonização - Gonçalves, Paulo Cesar [UNESP]; Oliveira, Lélio Luiz De; Mont Serrath, Pablo Oller (Universidade Estadual Paulista Julio de Mesquita Filho, 2020)
Under the perspective of the History of Economy, this article contextualizes the historiography of the proposal of the dossier History of colonization in the territory of Sao Paulo: dynamics and transformations (16th and 20th centuries) and presents the other 13 articles included. It is a propositional text that summarizes, within the context of expansion and consolidation of capitalism, the specific links among commercial trade, labour, organization of the productive lands and organization of the movements of the population as a political and economic practice in the territory of São Paulo. The main objective is to make a historiographical assessment of the meanings of colonization that defined the integration and expansion of the bonds between Sao Paulo, the world market and the development of the inner market, offering certain diversity of the agricultural production, so often suppressed by large exportation crops.

Sob a perspectiva da História Econômica, este artigo contextualiza em termos historiográficos a proposta do dossiê História da colonização em terras paulistas: dinâmicas e transformações (séculos XVI-XX) e apresenta os outros treze artigos que o compõem. Trata-se de um texto propositivo e de síntese que, dentro do quadro de expansão e consolidação do capitalismo, aborda os enlaces específicos entre trocas comerciais, mundos do trabalho, organização do espaço produtivo e ordenação dos movimentos de população como prática política e econômica no território paulista. O objetivo principal é fazer um balanço historiográfico sobre os sentidos da colonização que configuraram a integração e a ampliação dos laços entre São Paulo e o mercado mundial e o desenvolvimento do mercado interno, proporcionando certa diversidade da produção agrícola, muitas vezes obscurecida pela grande lavoura exportadora.
São Paulo and the meanings of colonization
Keywords: Colonization; São Paulo; Historiography; Economic Frontier; Demographic Frontier; Colonização; São Paulo; Historiografia; Fronteira econômica; Fronteira demográfica